2021
DOI: 10.1055/a-1522-4507
|View full text |Cite
|
Sign up to set email alerts
|

An Older Thrombus Delays Reperfusion after Mechanical Thrombectomy for Ischemic Stroke

Abstract: Background: Thrombosis is a dynamic process, and a thrombus undergoes physical and biochemical changes that may alter its response to reperfusion therapy. This study assessed whether thrombus age influenced reperfusion quality and outcomes after mechanical thrombectomy for cerebral embolism. Methods: We retrospectively evaluated 185 stroke patients and thrombi that were collected during mechanical thrombectomy at three stroke centers. Thrombi were pathologically classified as fresh or older based on their gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
(95 reference statements)
1
14
0
Order By: Relevance
“…Additionally, Kitano et al demonstrated that older thrombi had higher NET concentrations compared to fresh thrombi. Moreover, more device passes were required to retrieve older thrombi and achieve reperfusion, and this led to worse functional outcomes after mechanical thrombectomy [ 39 ]. Novotny et al confirmed the abovementioned hypothesis, showing that NETs were associated with firmer thrombus composition and worse clinical outcomes, assessed by NIHSS score [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Kitano et al demonstrated that older thrombi had higher NET concentrations compared to fresh thrombi. Moreover, more device passes were required to retrieve older thrombi and achieve reperfusion, and this led to worse functional outcomes after mechanical thrombectomy [ 39 ]. Novotny et al confirmed the abovementioned hypothesis, showing that NETs were associated with firmer thrombus composition and worse clinical outcomes, assessed by NIHSS score [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Cha et al failed to show any significant correlation between neutrophil count and either recanalization after thrombectomy (using TICI score as an assessment tool) or onset to recanalization time [ 33 ], but Ducroux et al demonstrated that NET content in thrombi was associated with endovascular procedure length and device number of passes [ 16 ]. Zeng et al also proved that H3Cit thrombus fractions were significantly higher in the delayed recanalization time group [ 21 ], whereas Kitano et al presented that older thrombi had a greater extent of NETosis and that more device passes before reperfusion were necessary for older thrombi and were associated with poorer functional outcomes [ 39 ]. Moreover, data from a study conducted by Orban et al elucidated that after thrombolysis, NET markers significantly increased in the no-improvement group.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, recent research has highlighted additional components beyond traditional ones, such as leukocytes, neutrophil extracellular traps, von Willebrand factor, tissue factor, and a few coagulation factors. [9][10][11][12][13][14] The mechanical properties of thrombi can be affected by individual components or by interactions between them, leading to unexpected heterogeneity in thrombus characteristics based on histological composition. Second, although researchers have made progress in identifying and staining thrombus components, there is still no standardized approach to this task.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombi can become stiffer and more resistant to thrombolysis over time ( 15, 16 ). We have previously reported that older thrombi are more resistant to reperfusion therapy in patients with cerebral embolism ( 17 ). Hence, it can be assumed that there are conflicting processes within a formed thrombus: some to make it stiff and stable and others to dissolve it.…”
Section: Introductionmentioning
confidence: 99%